Gibberellic Acid and Potassium Nitrate Promote Seed Germination and Growth of Grey-leaved Saucer-berry (Cordia Sinensis Lam.) Seedlings. (14th September 2020) - Dev, Rahul; Dayal, Devi; Sureshkumar, M.
ABSTRACT: Cordia sinensis: Lam is a multipurpose underutilized species of arid and semiarid regions. It is commonly propagated through seeds, but germination percentage is low (50–60%) and erratic. Therefore, an investigation was undertaken to standardize the propagation technique during year 2016 at CAZRI RRS Bhuj, India. The seeds of Cordia gharaf were treated with gibberellic acid (four levels: 0, 250, 500, and 1000 ppm) and potassium nitrate (four levels: 0%, 0.25%, 0.5%, and 1%) singly or in combination and it was found that combined application of GA3 and KNO3 enhanced seed germination synergistically ( p = .05). The treatment consisted of GA3 250 ppm and KNO3 (1%) resulted in earliest seed germination (4.33 ± 0.33 days), maximum seed germination percentage (79.47%), and subsequent seedling growth e.g . highest leaf area (25.52 ± 1.41 cm 2 ), and maximum leaf fresh (1.59 g) and dry weight (0.72 g). However, maximum plant height was observed under GA3 500 ppm and KNO3 (1%) treatment. In conclusion, the combination treatment of GA3 250 ppm and KNO3 1% is an effective and practical method for improving C. sinensis seed germination.